Asset Safety versus Asset Liquidity - Athanasios Geromichalos; Lucas Herrenbrueck; Sukjoon Lee (University of California, Department of Economics, 2018)
Recently, a lot of attention has been paid to the role “safe and liquid assets” play in the macroeconomy. Many economists take as given that safer assets will also be more liquid, and some go a step further by practically using the two terms as synonyms. However, they are not synonyms: safety refers to the probability that the (issuer of the) asset will pay the promised cash flow, and liquidity refers to the ease with which an asset can be sold if needed. Mixing up these terms can lead to confusion and wrong policy recommendations. In this paper, we build a multi-asset model in which an asset's safety and liquidity are well-defined and distinct from one another. Treating safety as a primitive, we examine the relationship between an asset's safety and liquidity in general equilibrium. We show that the commonly held belief that “safety implies liquidity” is generally justified, but there may be exceptions. We then describe the conditions under which a relatively riskier asset can be more liquid than its safe(r) counterparts. Finally, we use our model to rationalize the puzzling observation that AAA corporate bonds are considered less liquid than (the riskier) AA corporate bonds.
Keywords: E31; E43; E52; G12; 330; asset safety; asset liquidity; over-the-counter markets; liquidity premium